PRAKTIK PENYELESAIAN SENGKETA PERTANAHAN SECARA LITIGASI - RISDIANA RISDIANA (GANEC SWARA, 2024)
Article 33 paragraph (3) of the 1945 Constitution, which states that: "Earth and water and the wealth contained therein are controlled by the State and used for the greatest prosperity of the people." Epistemologically, this shows that there are at least two main things relating to the relationship between the State, the people and the region (agrarian). The agrarian problem starts from the very prominent inequality in land tenure structures. The control structure in this case is the distribution or distribution arrangement, both regarding ownership and control over agrarian resources, including the distribution of allocation or allocation. Many agrarian conflicts occur between communities, many land conflicts that occur within communities are resolved through mediation both at the village level and at the regional level with the existence of mediation halls that have been prepared by the government of each region, but if a deliberative settlement does not meet the results then the final step is The solution taken is settlement through litigation. Litigation is used by the community, bringing it to court (in the form of a dispute), to implement/enforce a certain right, through a judicial process (competition of evidence), to obtain a favorable decision